THE ECLIPSE OF SUBJECTIVITY AND IDEALIZATIONS OF THE 'OTHER' - Aileen Hewitt, Marsha (Journal of Dharma, 1997)
Perhaps the most important debate within contemporary feminist theory concerns questions of autonomous identity and of subjectivity in the struggle for the full emancipation of women. This debate fractures along the fault lines of modernity and postmodernity, where the legacies of the former, such as its belief in the transformative and emancipatory power of reason and in the capacity of autonomous moral subjects to bring about greater justice and a more humane world in cooperation with others are currently under heavy attack by the latter. I The focus of this paper is to examine one of the key issues contested by postmodernism that is of crucial importance to feminism: the concept of the autonomous subject.